TAR(p)/ARCH(1) Process with an Arbitrary Threshold: Guaranteed Parameter Estimation and Change-Point Detection; IAENG International Journal of Applied Mathematics; Vol. 46, iss. 3 - Vorobeychikov S. E. Sergey Erikovich (2016, 2016)
Title screen